1979
DOI: 10.1073/pnas.76.8.4084
|View full text |Cite
|
Sign up to set email alerts
|

Induction of indoleamine 2,3-dioxygenase in mouse lung during virus infection.

Abstract: Indoleamine 2,3-dioxygenase [indoleamine: oxygen 2,3-oxidoreductase (decyclizing)] activity in the supernatant fraction (30,000 X g, 30 min) of mouse lung homogenate increased approximately 120-fold after infection with PR8 influenza virus. Both specific and total enzyme activities started to increase linearly from the 5th day after infection, reached the highest level around the 11th day, and then gradually decreased to normal values in about 3 weeks. Other enzymes in the lung, such as certain lysosomal enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
129
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(138 citation statements)
references
References 17 publications
(7 reference statements)
9
129
0
Order By: Relevance
“…IDO induction in macrophages has been demonstrated during viral (39) and bacterial infection (40). High activity of IDO could aid the inhibition of bacterial growth since tryptophan is often an essential amino acid for bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…IDO induction in macrophages has been demonstrated during viral (39) and bacterial infection (40). High activity of IDO could aid the inhibition of bacterial growth since tryptophan is often an essential amino acid for bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The invasion of bacteria, parasites, or viruses induces a strong interferon-c (IFN-c)-dependent inflammatory response. Because IFN-c is a strong IDO inducer and intracellular pathogens require trp, it was demonstrated that a depletion of free trp by IDO controls intracellular pathogens (12). A decade ago, Munn and Mellor provided evidence for a much broader immunoregulatory significance of trp degradation.…”
Section: Tryptophan and Its Degradation Pathways: Indoleamine 23-diomentioning
confidence: 99%
“…IllNo. 4 induced by viruses, bacterial exotoxins and interferona (24,54). It is mentioned, that IDO takes part in the elevated kynurenine formation in pathological as well as in host defence mechanisms (54).…”
Section: Pteridineslvol 11 Rnomentioning
confidence: 99%